The influence of cognition and emotion on Nigerian undergraduates frustration during e-Registration - Alaba Olaoluwakotansibe Agbatogun,; Peter Ayo Ajelabi,; Lawunmi M. Oyewusi, (Penerbit Universiti Kebangsaan Malaysia, 2011)
This study was designed to investigate the relative and combined contributions of cognition and emotion to Nigerian undergraduates’ level of computer frustration in online environments. The 1972 students who participated in the study were randomly selected from the two state-owned universities in Ogun State, Nigeria. The data for the study were collected through the use of the Students’ Cognition Scale, Students’ Emotion Scale, and Students’ Computer Frustration Scale. Data analysis involved the use of mean and standard deviation as descriptive statistics, as well as the Pearson Product Moment Correlation and regression analysis as inferential statistics. The research findings revealed that students encountered various frustrating experiences during e-Registration and that a combination of the predictor variables, cognition and emotion, significantly accounted for 2.5% of the variance in the students’ level of frustration. Cognition was found to be the more potent contributor to this frustration. The results of this study further indicated that there was a statistically significant difference in the level of computer frustration among students at the two universities, potentially due to the relative differences in the schools’ technology facilities. Recommendations are made at the end of this paper in accordance with the findings of the study.